Rain fade estimations for the X-Band satellite communication link in the tropics - Nuroddin, Amirah; Ismail, Ahmad Fadzil; Abdullah, Khaizuran; Badron, Khairayu; Ismail , Maszlan; Hashim, Wahidah (International Association of Computer Science and Information Technology Press, 2013)
The X-band satellite communication (satcom) has been conventionally set aside for military and government organizations. It is also commonly known as the military band. The attributes of an X-band satcom hardware are expected to be designed specifically for military operations and they are expected to differ very much to those of commercial frequencies. The satcom will be likely to be exclusively designed to support smaller, low powered, tactical terminals deployed across various theatres of operation. In addition, X-band link is also anticipated to offer a more substantial increased of system capacity due to its higher frequencies compared to the forerunner S-band and C-band. The X-band satcom technology is drawing growing interest from military users including of the Malaysian authorities. However, there are many aspects of X-band that are harder to realize than of those of at lower frequencies. X-band frequencies certainly have higher atmospheric propagation losses, higher RF losses, and certainly much severe signal degradation due to rain. It is would be in the best interest of the satellite designers and engineers alike to accurately appraise the challenges of an X-band satcom link especially in the case of tropical regions where heavy rains are copious whilst the required technological advancements are in pursuit.